PERBANDINGAN SOIL IMPROVEMENT PADA TANAH LAPUKAN BATUAN VULKANIK DI JATINANGOR, KABUPATEN SUMEDANG, DAN TANAH LAPUKAN BATUAN VULKANIK DI CIGINTUNG, MALAUSMA, KABUPATEN MAJALENGKA - Zakaria, Zufialdi; Sophian, Irvan; Chaniago, Aulia Eka P S (Bulletin of Scientific Contribution, 2017)
ABSTRACTSoil improvement is one of the methods of soil reinforcement. One method of soil improvement is the addition of soil with lime (CaO). The swelling soil (expanding when wet conditions, and shrinking when dry conditions) is identified from the value of soil activity. The behavior of soil activity decreases with increasing CaO, but for soils in weathered volcanic areas (volcanic breccia and lava) as in Jatinangor, with the value of high soil activity, the optimum addition of CaO to the soil is 15% and not more than 20%. Excessive addition of CaO tends to change the behavior of soil activity and increase the rate of activity. In the soil from weathered volcanic rock (tuff) as in Cigintung Village, District Malausma, in Majalengka, with the value of moderate to high soil activity, the addition of CaO is 15% to 20%. More than 20% CaO, activity number (A) decreases, but cohesion (c, Kg/M2) will decrease too, so the strength of soil will decrease.  Keywords: swelling, activity number, soil improvement,  ABSTRAKPerbaikan tanah (soil improvement) adalah salah satu metode perkuatan tanah. Salah satu metode soil improvement adalah penambahan tanah dengan kapur (CaO). Tanah yang bersifat swelling (mengembang bila basah dan mengerut bila kering) diidentifikasi dari nilai aktivitas tanahnya. Perilaku aktivitas tanah berkurang dengan bertambahnya  CaO. Untuk tanah di daerah lapukan vulkanik (breksi vulkanik dan lava) seperti di Jatinangor, dengan nilai aktivitas tinggi, penambahan CaO yang optimum pada tanah mengembang adalah 15 % dan tidak lebih dari 20 %. Penambahan CaO yang berlebihan cenderung mengubah perilaku aktivitas tanah dan meningkatkan kembali angka aktivitas. Pada tanah lapukan batuan vulkanik (tuff) seperti di desa Cigintung, Kecamatan Malausma, di Kabupaten Majalengka, dengan aktivitas tanah sedang sampai tinggi, penambahan CaO cukup 15% sampai 20%. Lebih dari 20% CaO, maka angka aktivitas turun, namun kohesi akan turun pula sehingga kekuatan tanah justru akan berkurang. Kata kunci: swelling, angka aktivitas, perbaikan tanah